Global rice and agricultural trade liberalisation : poverty and welfare implications for South Asia - Laurent, Edwin; Razzaque, Mohammad A.; Commonwealth Secretariat (London : Commonwealth Secretariat ; New Delhi : Academic Foundation, 2008)
Contributed articels.
Fakulti Agro Industri dan Sumber Asli.
Includes statistics.
Includes bibliographical references (p. 211-217) and index.
Keywords: Rice trade -- Government policy -- South Asia -- Mathematical models; Rice trade -- South Asia -- Mathematical models; Rice -- Economic aspects -- South Asia -- Mathematical models